Impact of maternal age on birth weight-related adverse outcomes in newborns: a retrospective study in south-central China - Zhi Huang; Yan Zhang; Jinlian Wang; Xia Tan; Aiping Zhang (BMC Pregnancy and Childbirth)
Abstract Background Birth weight is a critical indicator for assessing fetal development and newborn health status. This study aimed to examine both linear and nonlinear associations between maternal age and birth weight and their related adverse outcomes. Methods 15,923 delivery data from 2018 to 2021 for pregnant women from the Changsha Maternal and Child Health Care Hospital were reviewed by a retrospective study. Basic information and infant birth weight were retrieved from the Medical Birth Registry. Multivariable regression models and the restricted cubic splines (RCS) analysis were used to identify the associations between maternal age and birth weight and its related adverse outcomes. Results The ages of pregnant women trended upward from 2018 to 2021. Maternal age had a nonlinear association with birth weight (P for nonlinear = 0.028). Gestational weeks had a masking effect on the association between maternal age and birth weight, with an effect value of -7.368. A nonlinear association was found between maternal age and macrosomia (P for nonlinear = 0.009). Maternal age increased the risk for large for gestational age (LGA) (OR = 1.016, 95% CI: 1.006–1.027, P = 0.002) and preterm birth (OR = 1.028, 95% CI: 1.008–1.049, P = 0.005). Conclusions This retrospective study from south-central China indicates that pregnant women are getting older and maternal age is nonlinearly associated with birth weight, while this association is masked by gestational weeks. Advanced maternal age increases the risk for heavier birth weight-related adverse outcomes.